Guest Editors’ Note: The Directions And Challenges Of Regional Islamic Higher Education Institutions Within The Modernization And Fourth Industrial Revolution - Khatijah Othman; Fauziah Hassan (USIM Press, 2024)
Vol. 23 No. 2 (2020): Journal of Islamic Social Sciences and Humanities (Special Issue)